Integrasi Agama dan Sains Dalam Perspektif Abdussalam - Hotma Ida Br. Simamora; Amril Amril; Eva Dewi (JURNAL ILMIAH NUSANTARA, 2024)
This article reviews the life and thoughts of Professor Abdus Salam, a prominent Muslim scientist who received the Nobel Prize in Physics in 1979. Professor Abdus Salam presented his contribution to theoretical physics by basing his thinking on the values ​​of the Koran. Apart from his scientific achievements, Salam also plays a role as a politician who maintains moral integrity in the world of politics. This article explains the challenges Salam faced, including the intellectual isolation he experienced in Pakistan, as well as his struggle to integrate religion and science. Apart from that, the article also discusses Salam's perspective on the need to integrate science and religious values ​​in the Islamic education system to create a more advanced and civilized civilization.